Nanocomposite Made of an Oligo(p‐phenylenevinylene)‐Based Trihybrid Thixotropic Metallo(organo)gel Comprising Nanoscale Metal–Organic Particles, Carbon Nanohorns, and Silver Nanoparticles. Issue 14 (12th February 2015) - Bhattacharjee, Subham; Samanta, Suman K.; Moitra, Parikshit; Pramoda, K.; Kumar, Ram; Bhattacharya, Santanu; Rao, C. N. R.
Abstract A silver ion (Ag+)‐triggered thixotropic metallo(organo)gel of p‐pyridyl‐appended oligo(p‐phenylenevinylene) derivatives (OPVs) is reported for the first time. Solubilization of single‐walled carbon nanohorns (SWCNHs) in solutions of the pure OPVs as well as in the metallogels mediated by π–π interactions has also been achieved. In situ fabrication of silver nanoparticles (AgNPs) in the SWCNH‐doped dihybrid gel leads to the formation of a trihybrid metallogel. The mechanical strength of the metallogels could be increased stepwise in the order: freshly prepared gel<dihybrid gel<trihybrid gel. Microscopic studies of the trihybrid gel indicate the formation of three distinct morphologies, that is, nanoscale metal–organic particles (NMOPs), flowerlike aggregates of SWCNHs and AgNPs, and also their integration with each other. Detailed studies suggest lamellar organizations of the linear metal–ligand complexes in the NMOPs, which upon association create a three‐dimensional network that eventually immobilizes the solvent molecules.